Guava ripening and quality in response to pre-harvest boron spraying - Filho, Vitor Hugo Artigiani [UNESP]; Leonel, Sarita [UNESP]; Putti, Fernando Ferrari [UNESP]; Martins, Rafaelly Calsavara [UNESP]; Ferreira, Rafael Bibiano [UNESP] (Southern Cross Publishing, 2024)
The physiological process of guava fruit ripening is difficult to manage in orchards. Boron (B) is a nutritional element with a physiological effect on fruit ripening through its role in ascorbate metabolism. This study evaluated the effects of single boron pre-harvest spraying on fruit ripening and post-harvest. The treatments consisted of B-monoethanolamine (MEA) sprays (11% B) at concentrations of 0 (control), 1, 2, and 3ml L-1. Foliar sprays were applied on guava trees cv. Cortibel RG, at the physiological stage Biologische Bundesanstalt, Bundessortenamt, und Chemische Industrie (BBCH) 78 (fruits at 80% of final growth). The study used a randomized block design with five replicates. Fruits were harvested 5, 8, 15, and 17 days after B-MEA spraying. The nutritional content was assessed in the leaves and fruits. The fruits were analyzed for ascorbic acid content (AA), total sugars, reducing and non-reducing sugars, titratable acidity, soluble solids, ripeness index, total phenolic compounds, total carotenoids and total anthocyanins. Moreover, the fruit weight, length and diameter were measured and yield were assessed. Fruit firmness and mass loss were evaluated post-harvest. The data showed an increase in ascorbic acid content in the fruit in all treatments with B-MEA sprays. Spraying B-MEA 3 ml L-1, or 180.84 g ha-1, increased the earliness and standardization of ripening, which took place over a shorter period of time, maintaining firmness and reducing postharvest fruit mass loss.
Keywords: ascorbic acid; bioactive compounds; foliar spray; fruit maturation; nutritional content; Psidium guajava, L